A new large-flowered Cyrtochilum (Orchidaceae: Oncidiinae) from Ecuador, named in honor of two orchid research legends - Daström, Stig (Lankesteriana: International Journal on Orchidology, 2017)
A new and attractive but little-known Cyrtochilum (Orchidaceae: Oncidiinae), which was previously misidentified as Cyrtochilum aemulum, is named in honor of the 95th birthdays of Carlyle August and Jane Hortense Pfeiffenberger Luer of Sarasota, Florida, the most prolific orchid research couple the world has ever known. The background of how the author first became acquainted with the legendary researchers is featured here together with color photographs of them taken by the author on various occasions during their long career. The new Cyrtochilum is described, illustrated and compared with the rather similarly colored C. aemulum. The new species is distinguished from it by the combination of geniculated and shortly spathulate bases of the petals and a glabrous, more erect and more complex lip callus versus shortly unguiculate bases of the petals and a finely micro-pubescent and a horizontally flatter and more simple lip-callus of C. aemulum.